Alleviation of power fluctuation in a microgrid by electrolyzer based on optimal fuzzy gain scheduling PID control - Chaiyatham, Theerawut; Ngamroo, Issarachai (My University, 2014)
This paper presents an application of the electrolyzer (EZ) to alleviate the power fluctuation in a microgrid with hybrid power generations from wind, photovoltaic array, fuel cell, and diesel engine. In this microgrid, the intermittent power generations from wind and photovoltaic arrays cause severe power fluctuation. With the fast response of EZ, the power absorbed by EZ can be controlled to compensate for the power fluctuation, in addition to the hydrogen production for fuel cell. The structure of the active and reactive power controllers of EZ is the fuzzy gain scheduling of a proportional-integral-derivative (FGS-PID) controller. Without trial and error, the scale factors, membership functions, and control rules of the FGS-PID controller are automatically optimized by bee colony optimization. A simulation study confirms that the proposed EZ with optimal FGS-PID controller is much superior to the optimal PID controller in terms of damping effect, robustness against disturbances, and hydrogen production. © 2014 Institute of Electrical Engineers of Japan.
Keywords: Bee colony optimization; Electrolyzer; Fuzzy gain scheduling; Microgrid